2021
DOI: 10.1002/cjce.24271
|View full text |Cite
|
Sign up to set email alerts
|

Chemomechanical effects of oxidizer‐CO2 systems upon hydraulically fractured unconventional source rock

Abstract: Carbon dioxide (CO2) as supercritical (scCO2) or foamed (CO2‐Foam) fluid has been tested many times as a fracturing fluid, though it has not yet proven viable. Many challenges have been identified with scCO2 as a fracturing fluid, including poor additive solubility, low viscosity, and limited accessibility. However, CO2 is known to adsorb to organic matter (OM) and displace methane (i.e., enhanced coal bed methane [ECBM] operations), or to mobilize oil as in tertiary enhanced oil recovery. In this study we aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The other transition of oxygen from BrO À 3 to an oxygen-derived propyl backbone leads to the formation of a CÀ O bond while a CÀ C bond of the propyl species breaks apart, as observed in the TS profile of both ReaxFF and DFT. This step releases ethoxy radical and formaldehyde molecules, which contain a hydrophilic carbonyl polar functional group, in agreement with 13 C solid-state NMR measurements by Hull et al [18] Oxidation of an aromatic hydrocarbon In Figure 4(b), we observe a proton transfer to the oxygen atom of BrO À 4 in the first stage of the oxidation reaction. This reaction structure illustrates how the presence of BrO À 4 can strongly influence the structural deformation of benzene and induce intense vibrations.…”
Section: Oxidation Of Aliphatic Hydrocarbonssupporting
confidence: 88%
See 3 more Smart Citations
“…The other transition of oxygen from BrO À 3 to an oxygen-derived propyl backbone leads to the formation of a CÀ O bond while a CÀ C bond of the propyl species breaks apart, as observed in the TS profile of both ReaxFF and DFT. This step releases ethoxy radical and formaldehyde molecules, which contain a hydrophilic carbonyl polar functional group, in agreement with 13 C solid-state NMR measurements by Hull et al [18] Oxidation of an aromatic hydrocarbon In Figure 4(b), we observe a proton transfer to the oxygen atom of BrO À 4 in the first stage of the oxidation reaction. This reaction structure illustrates how the presence of BrO À 4 can strongly influence the structural deformation of benzene and induce intense vibrations.…”
Section: Oxidation Of Aliphatic Hydrocarbonssupporting
confidence: 88%
“…Notably, dicoronylene exhibits fewer instances of CÀ C bond breakage and less fragmented molecular species, underscoring the greater energetic stability of aromatic hydrocarbons against bond breaking compared to aliphatic hydrocarbons. This was experimentally observed in 13 C solid-state NMR measurements by Hull et al that showed aromatic moieties of kerogen remain less degraded after three hours of exposure to oxyhalides as compared to aliphatic moieties. They showed aromatic structures substantially degraded after twenty hours, indicating a more sluggish reaction.…”
Section: Quantitative Analysis Of the Oxidation Processmentioning
confidence: 52%
See 2 more Smart Citations
“…The Canadian Journal of Chemical Engineering is acknowledged for dedicating this special issue to the living memory of Dr. Nasr‐El‐Din. This acknowledgment is also extended to the authors who contributed to this special issue [ 1–28 ] as well as the guest editors:…”
mentioning
confidence: 99%